Concussions and heading in soccer: A review of the evidence of incidence, mechanisms, biomarkers and neurocognitive outcomes. (March 2014) - Maher, Monica E.; Hutchison, Michael; Cusimano, Michael; Comper, Paul; Schweizer, Tom A.
Abstract Background: Soccer is currently the most popular and fastest-growing sport worldwide. Similar to many sports, soccer carries an inherent risk of injury, including concussion. Soccer is also unique in the use of 'heading'. The present paper provides a comprehensive review of the research examining the incidence, mechanisms, biomarkers of injury and neurocognitive outcomes of concussions and heading in soccer. Methods: Seven databases were searched for articles from 1806 to 24 May 2013. Articles obtained by the electronic search were reviewed for relevance, with 229 selected for review. Ultimately, 49 articles met criteria for inclusion in the present review. Results: Female soccer players have a higher incidence of concussions than males. The most frequent injury mechanism is player-to-player contact for both genders. Few studies examined the effects of concussion in soccer players; however, neurocognitive outcomes were similar to those reported in the larger sport concussion literature, while the effect of heading is less clear. Conclusion: Despite variation in research designs and study characteristics, the outcomes of concussions in soccer align with the greater concussion literature. This review makes recommendations for future research to increase standardization of research for improved understanding of concussions in soccer as well as the effects of heading.